2018
DOI: 10.1021/acs.jpcb.7b11370
|View full text |Cite
|
Sign up to set email alerts
|

Two-Dimensional Spectroscopy Is Being Used to Address Core Scientific Questions in Biology and Materials Science

Abstract: Two-dimensional spectroscopy is a powerful tool for extracting structural and dynamic information from a wide range of chemical systems. We provide a brief overview of the ways in which two-dimensional visible and infrared spectroscopies are being applied to elucidate fundamental details of important processes in biological and materials science. The topics covered include amyloid proteins, photosynthetic complexes, ion channels, photovoltaics, batteries, as well as a variety of promising new methods in two-di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
59
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(60 citation statements)
references
References 127 publications
0
59
0
1
Order By: Relevance
“…The proliferation of two-dimensional optical spectroscopy (2DOS) has revolutionised research into the structure and dynamics of chemical systems. [1][2][3] The detection of coherent quantum superpositions can identify electronic couplings and the existence of excitonic states, as well as vibronic couplings and the motions of nuclear wavepackets on a potential energy surface. 4,5 The study of such coherences requires the use of ultrafast spectroscopic techniques, where 2DOS provides a means of differentiating individual coherence pathways.…”
Section: Introductionmentioning
confidence: 99%
“…The proliferation of two-dimensional optical spectroscopy (2DOS) has revolutionised research into the structure and dynamics of chemical systems. [1][2][3] The detection of coherent quantum superpositions can identify electronic couplings and the existence of excitonic states, as well as vibronic couplings and the motions of nuclear wavepackets on a potential energy surface. 4,5 The study of such coherences requires the use of ultrafast spectroscopic techniques, where 2DOS provides a means of differentiating individual coherence pathways.…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless their potential in routine analytical diagnosis is not yet well established and this is especially true for the non-linear techniques [1,2]. The effort to disentangle specific structural information from complex spectra of complex molecular systems is still a challenge [3]. Many studies are presently reported on short medium and even large molecular systems [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…The effort to disentangle specific structural information from complex spectra of complex molecular systems is still a challenge [3]. Many studies are presently reported on short medium and even large molecular systems [3,4]. The aim is to disentangle homogeneous pieces of information out of broad inhomogeneous signals.…”
Section: Introductionmentioning
confidence: 99%
“…With recent advancements in lasers and optics, MDS experiments are becoming routine. Applications of MDS in semiconductor photophysics [CTK + 15], medicine [FGG + 09], and other domains [PLMZ18] are currently being developed. Ultimately, MDS may become a key research tool akin to multidimensional nuclear magnetic resonance spectroscopy.…”
Section: Introductionmentioning
confidence: 99%